2000
DOI: 10.1046/j.1365-2443.2000.00364.x
|View full text |Cite
|
Sign up to set email alerts
|

Molecular analysis of zebrafish photolyase/cryptochrome family: two types of cryptochromes present in zebrafish

Abstract: Background: Cryptochromes (CRY), members of the DNA photolyase/cryptochrome protein family, regulate the circadian clock in animals and plants. Two types of animal CRYs are known, mammalian CRY and Drosophila CRY. Both CRYs participate in the regulation of circadian rhythm, but they have different light dependencies for their reactions and have different effects on the negative feedback loop which generates a circadian oscillation of gene expression. Mammalian CRYs act as a potent inhibitor of transcriptional … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

18
189
0
7

Year Published

2002
2002
2016
2016

Publication Types

Select...
4
2
2

Relationship

2
6

Authors

Journals

citations
Cited by 188 publications
(214 citation statements)
references
References 51 publications
18
189
0
7
Order By: Relevance
“…53,61) Investigation of the in vitro functions of these genes has shown that they fall into two groups: one group inhibits CLOCK:BMAL-mediated transcription (repressor type CRYs: zCRY1a, 1b, 2a and 2b), whereas the other group does not inhibit transcription (non-repressor type CRYs: zCRY3, 4 and Dash). 61,62) Despite its structural and functional similarities to the repressor type CRYs, zCry1a transcription is quite different from that of the other repressor type CRYs and is strictly light-dependent (Fig. 1, top).…”
Section: Redox Signaling Is Involved In the Light Entrainment Of The mentioning
confidence: 99%
“…53,61) Investigation of the in vitro functions of these genes has shown that they fall into two groups: one group inhibits CLOCK:BMAL-mediated transcription (repressor type CRYs: zCRY1a, 1b, 2a and 2b), whereas the other group does not inhibit transcription (non-repressor type CRYs: zCRY3, 4 and Dash). 61,62) Despite its structural and functional similarities to the repressor type CRYs, zCry1a transcription is quite different from that of the other repressor type CRYs and is strictly light-dependent (Fig. 1, top).…”
Section: Redox Signaling Is Involved In the Light Entrainment Of The mentioning
confidence: 99%
“…Despite sharing a well conserved primary structure, the three CRYs differ markedly in their functional activities. zCRY1a, as well as mCRY1, represses CLOCK:BMAL-mediated transcription, whereas zCRY3 does not (16,20). We took advantage of the similarities between the nucleotide/amino acid sequences and the differences in transcriptional repressor activities of zCRY1a and -3 to produce zCRY1a-3 chimeras, which permitted mapping of the region responsible for transcriptional repressor activity.…”
Section: Construction Of Chimeric Zcrys With Exchanged Zcry1a and Zcry3mentioning
confidence: 99%
“…Four repressor-type zCRYs (zCRY1a, -1b, -2a, and -2b) have been identified in zebrafish. They repress the activities of mouse CLOCK and BMAL, as well as those of zebrafish CLOCK and BMAL, indicative that the basic function of re-pressor-type zCRYs is the same as that of mCRYs (16,19,20). A unique feature of zebrafish CRY is the presence of extra paralogous genes.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…This type of Cry does not inhibit CLOCK:BMAL1-mediated transcription, but functions instead as a light-dependent suppressor of PER/TIM-mediated inhibition of transcription (Ceriani et al, 1999). Former studies on zebrafish have shown that there are six Cry proteins, with Cry1aa, Cry1ab, Cry1ba and Cry1bb being mammalian-like, and Cry2 and Cry4 being Drosophila-like (Kobayashi et al, 2000;Liu et al, 2015;Zhou et al, 2016). The evolutionary relationship between zebrafish cry genes and other animals were also explored, and different nomenclature systems were introduced in the above studies.…”
Section: Discussionmentioning
confidence: 99%